Factors affecting customer satisfaction in fitness clubs: Study from Kathmandu Valley - Khadka, Ajaya Kumar; Khadka, Srijana (NCC Journal, 2022)
This study examined the factors influencing consumer satisfaction in fitness clubs, focusing on affordability (price), location, advertising, and equipment quality. The objective was to provide fitness facility owners and managers with information to enhance their services and retain customers. Although equipment quality is essential, other factors may affect customer satisfaction. The regression analysis results indicate that affordability, location, and advertising significantly impact customer satisfaction, while equipment quality does not. These findings highlight the need for fitness clubs to prioritize accessibility, affordability, and effective advertising to increase consumer satisfaction. In a highly competitive industry, fitness clubs can optimize customer experiences and enhance overall business performance by understanding these factors.